Cholera pulse vaccination: A possible elimination strategy for cholera in endemic countries - Neelam Taneja; Swati Gupta; Jutang Babat Ain Tiewsoh; Sonakshi Srivastava (Wolters Kluwer Medknow Publications, 2021)
Cholera is a diarrheal disease causing major health issue in developing countries where it is endemic and causes outbreaks. India ranks first with an estimated 675,188 number of cases and 20,256 number of deaths annually with one-third of its population at risk. The two broad approaches for cholera control are improving sanitation and vaccination. Now both live and killed oral vaccines are available. Live vaccines are advantageous in respect of intestinal colonization and rapid immune response and also lead to in vivo exposure of bacterial products leading to good immunological response against wild Vibrio cholerae infection. The three major delivery strategies which can be considered for the implementation of oral cholera vaccine are preemptive vaccination, reactive vaccinations, and National Immunization Program. We propose the use of cholera live oral vaccines for achieving control of this disease by repeated vaccination of the susceptible population in a series of pulses to control it from the entire population.